Horizontal gene transfer-mediated enhancement of gut antifungal defense facilitates host plant adaptation in an invasive pest - Shouke Zhang; Xiayu Li; Zikun Li; Yuxin Zhang; Yiping Wang; Letian Xu (Cell Reports, 2025)
Summary: Invasive pests exploit adaptive mechanisms including horizontal gene transfer (HGT) to overcome environmental challenges. Here, we show that the invasive fall webworm Hyphantria cunea acquires a chitinase gene (HcuChiA) via HGT, facilitating adaptation to the novel host Metasequoia glyptostroboides. Comparative transcriptomics across five host plants and an artificial diet identified HcuChiA as uniquely upregulated on M. glyptostroboides. Single-cell transcriptomics and spatiotemporal profiling confirmed gut-specific expression, and phylogenetic analysis traced HcuChiA to a bacterial donor. RNAi knockdown of HcuChiA increased the larval mortality on M. glyptostroboides, while recombinant HcuChiA displayed chitinase activity and broad-spectrum antifungal effects against entomopathogens. Elimination of gut fungi abolished the RNAi-induced mortality increase, demonstrating HcuChiA’s role in gut antifungal immunity. These findings reveal that HGT-derived enzymes enhance host expansion in invasive pests by strengthening immune defenses, offering insights into multi-host adaptation and the evolutionary significance of HGT.